2020
DOI: 10.1002/agj2.20092
|View full text |Cite
|
Sign up to set email alerts
|

Yield and potassium uptake of rice as affected by potassium rate in the middle reaches of the Yangtze River, China

Abstract: Yield and potassium uptake of rice as affected by potassium rate in the middle reaches of the Yangtze River, China Abstract Potassium is an essential macroelement for rice (Oryza sativa L.), but K deficiency in paddy ecosystems has increased widely and limited sustainable rice production in China. Two-year field trials were conducted with five K levels (0, 60, 120, 180, and 240 kg K 2 O ha -1 , designated as K0, K60, K120, K180, and K240) in Qichun county, Hubei Province, to investigate grain yield, K uptake c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The maximum yield increases from K fertilization measured in the five K‐responsive, pure‐line rice trials (Table 3) are comparable to the yield responses documented in the published literature (Fryer et al., 2019; Slaton et al., 2009; Slaton et al., 2010; Ye et al., 2020). Slaton et al.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The maximum yield increases from K fertilization measured in the five K‐responsive, pure‐line rice trials (Table 3) are comparable to the yield responses documented in the published literature (Fryer et al., 2019; Slaton et al., 2009; Slaton et al., 2010; Ye et al., 2020). Slaton et al.…”
Section: Discussionsupporting
confidence: 84%
“…The greater biomass and grain yield produced by hybrid cultivars compared with pure‐line cultivars (Mahajan & Chauhan, 2016; Slaton et al., 2010) would seem to increase the demand for and responsiveness to fertilizer K when grown on K‐deficient soils as suggested by Doberman and Fairhurst (2000). Hybrids have been shown to respond positively to K fertilization (Ye et al., 2020) and rice genotypes may respond differently to K fertilization (Yang et al., 2003). However, we could not find any literature suggesting consistent differences in response to K between pure‐line and hybrid cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…The logistic equation is one of the most frequently used nonlinear functions that have been developed to model important aspects of crop growth, including crop and kernel development, biomass accumulation [33][34][35]. It performed reasonably well in interpreting the dynamics of biomass and nutrient accumulation in major crops including rice [42,43], cotton [34,36], maize [44] and winter wheat [25]. In the present study, the simulated values of the aboveground biomass and N accumulation in winter oilseed rape cultivars were in good agreement with the measured values with R 2 of 0.919-0.999, RMSE of 1.0-14.1% and EF of 0.911-0.999, which could suggest reasonable accuracy in model simulation according to previous studies [27,45].…”
Section: Model Performancementioning
confidence: 99%
“…Potassium application could effectively increase the K contents of each organ, and higher K applications have yielded higher proportions of stem distribution. However, despite the absorption of stem potassium, no significant changes in grain K contents have been observed ( Ye et al., 2020 ). Potassium uptake by cereal crops mainly occurs before the flowering stage, and the K required during grain development is mainly obtained via transport from the vegetative organs ( Zhang et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cereal crops have high K demands, and the amount of K required for 100 kg of grain is 2-3 kg (Xie et al, 2009). Ye et al (2020) used the linear plus platform model to determine that the suitable potassium application rate for high rice quality and yield was kg•hm −2 of K 2 O. Sun et al (2014) suggested that 133.5 kg•hm −2 of K 2 O was suitable for millet in central Shanxi.…”
Section: Introductionmentioning
confidence: 99%